2016
DOI: 10.1093/hmg/ddw073
|View full text |Cite
|
Sign up to set email alerts
|

A small-molecule Nrf1 and Nrf2 activator mitigates polyglutamine toxicity in spinal and bulbar muscular atrophy

Abstract: Spinal and bulbar muscular atrophy (SBMA, also known as Kennedy's disease) is one of nine neurodegenerative disorders that are caused by expansion of polyglutamine-encoding CAG repeats. Intracellular accumulation of abnormal proteins in these diseases, a pathological hallmark, is associated with defects in protein homeostasis. Enhancement of the cellular proteostasis capacity with small molecules has therefore emerged as a promising approach to treatment. Here, we characterize a novel curcumin analog, ASC-JM17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 53 publications
6
47
1
Order By: Relevance
“…For instance, the life expectancy of transgenic mice expressing human mutant SNCA A53T is largely increased when crossed with mice overexpressing NFE2L2 in astrocytes 69 and the NFE2L2 activator dimethyl fumarate, already in clinical use for multiple sclerosis, reduces SNCA toxicity 70 . Other NFE2L2 activators are being studied for alleviation of proteinopathies such as spinal and bulbar muscular atrophy 71 . Future work will be needed to determine if pharmacological induction of NFE2L2 may be a valid strategy to facilitate degradation of toxic proteins in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the life expectancy of transgenic mice expressing human mutant SNCA A53T is largely increased when crossed with mice overexpressing NFE2L2 in astrocytes 69 and the NFE2L2 activator dimethyl fumarate, already in clinical use for multiple sclerosis, reduces SNCA toxicity 70 . Other NFE2L2 activators are being studied for alleviation of proteinopathies such as spinal and bulbar muscular atrophy 71 . Future work will be needed to determine if pharmacological induction of NFE2L2 may be a valid strategy to facilitate degradation of toxic proteins in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…) induces broad antioxidant effects in HD mouse brain and ameliorates the neurological phenotype . The benefits of Nrf2 activation can be extended to other polyglutamine diseases such as spinal and bulbar muscular atrophy (SBMA, also known as Kennedy's disease) .…”
Section: Nrf2‐dependent Amelioration Of Age‐dependent Neurological Phmentioning
confidence: 99%
“…While inactivation of SKN-1A/Nrf1 is catastrophic, our results suggest that enhancing SKN-1A/Nrf1 activity can enhance proteasome function and increase resistance to proteotoxic insults. A recent study found that a pharmacological activator of Nrf1 is protective in a mouse model of spinal and bulbar muscular atrophy (Bott et al, 2016).…”
Section: Png-1/ngly1 and Skn-1a/nrf1 Control Proteostasismentioning
confidence: 99%